Eksegesis Markus 10:11-12:Implikasi terhadap Kualifikasi Pelayanan dalam Perspektif Kasih Karunia - Eddy Danukusumah (JURNAL LUXNOS, 2026)
This study examines the interpretation of Mark 10:11-12, often understood as a permanent prohibition against divorced and remarried individuals serving in the church. It reviews whether Jesus' statement constitutes a permanent condemnation and explores its theological implications for ministry qualifications and the role of grace in pastoral restoration. The research employs qualitative biblical exegesis, incorporating first-century Jewish historical context, hermeneutical analysis of Mark 10:1-12, comparative study with parallel passages (Matthew 19, Luke 16, 1 Corinthians 7), and a synthesis of evangelical systematic theology literature and denominational documents. Findings indicate that Mark 10:11-12 is not a permanent verdict, but an affirmation of marriage as a lifelong covenant according to God's creational design. Jesus' statement is descriptive of covenant violation, not hopeless condemnation. Ministry qualifications must consider the circumstances of divorce, genuine repentance, character transformation, and church policy. The study concludes that divorce and remarriage are serious violations, yet remain within the reach of God's grace. The church is called to maintain a dialectical tension between marital holiness and transformative grace, developing a pastoral framework that provides a clear restoration pathway — free from legalism, grounded in wisdom and compassion.